Pediatric asthma and eosinophilia: insights from nasal and blood smear analyses - M. B., Shervani; M. R., Savitha; K. B., Esaivani (International Journal of Contemporary Pediatrics, 2024)
Background: Allergic respiratory maladies, particularly pediatric asthma, pose substantial challenges in public health. This cross-sectional investigation endeavours to unravel the eosinophilic landscape within nasal cytological specimens and peripheral blood samples of pediatric asthma cohorts, with a keen focus on discerning the correlation between nasal and systemic eosinophilia. Methods: Sixty-six pediatric asthma subjects, aged 6 to 18, under the care of Cheluvamba hospital in Mysuru, were meticulously recruited over an extensive 18-month period. Results: Analysis unveiled a conspicuous preponderance of male participants, with a mean age range spanning 9 to 13 years. Intriguingly, the presence of allergic rhinitis (AR) exhibited no discernible statistically significant nexus with either asthma severity or eosinophilic markers. Noteworthy findings include peripheral eosinophilia detected in 56% of subjects, juxtaposed against nasal eosinophilia observed in 20%; however, no statistically meaningful correlation emerged between nasal and peripheral eosinophilia. Conclusions: The inquiry culminated in a robust affirmation that mean nasal eosinophil count and blood absolute eosinophil count (AEC) exhibit a salient association with asthma severity and control in pediatric cohorts, irrespective of AR presence. Particularly, a discernible augmentation in mean AEC and nasal eosinophil count was discerned concomitant with exacerbating asthma severity and in cases of partial/ uncontrolled asthma.